Urban futures : critical commentaries on shaping the city - Miles, Malcolm, 1950 June 6-; Hall, Tim, 1968- (Routledge, 2003)
Urban Futures brings together commentaries from a wide range of contemporary disciplines and fields relevant to urban culture, form and society. The book concerns cities in the broadest sense, not just as buildings and spaces, but also as processes and events or sites of occupation, in which meanings are constructed in many ways. The contributors draw on their specialist areas of research to inform current debate, but they also speculate as to how cities will be shaped in the 21st century.